Dynamic electrical model of sealed lead-acid battery for EV simulation - Tariq, Rayyan; Sabbir, Sabiun; Azad, Sadia Afrin B. (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.